Adapted legumes as a dietary alternative to sheep in the semi-arid – a review (Revista de Ciências Agroveterinárias, 2015)
The objective of this review was to characterize the use of alternative legumes adapted to northeastern Brazil and to evaluate the effect of these on supply and production of sheep. Given the information, the importance of using these pulses to promote better productivity in northeastern Brazil in times of short supply of food for ruminants was noted and, thus, increased profitability in the sheep.
Keywords: gliricídia; leucaena; sheep.